In situ encapsulation of tin oxide and cobalt oxide composite in porous carbon for high-performance energy storage applications - Pal, Bhupender; Krishnan, Syam G.; Vijayan, Bincy Lathakumary; Harilal, Midhun; Yang, Chun-Chen; Ezema, Fabian I.; M. M., Yusoff; Rajan, Jose (Elsevier B.V., 2018)
Herein, we report the preparation of porous carbon from palm kernel shell and loading of tin oxide‑cobalt oxide in its pores using a facile in-situ encapsulation synthesis strategy. The as-synthesized SnO2/Co3O4@C composite was characterized by powder X-ray diffraction, X-ray photoelectron spectroscopy and field-emission scanning electron microscopy techniques. This composite was used as an electrode for supercapacitors. Electrochemical charge storage capabilities of the composite were measured using cyclic voltammetry, charge-discharge cycling and electrochemical impedance spectroscopy in aqueous 6 M KOH and 1 M Na2SO4 electrolytes. The SnO2/Co3O4@C composite showed over 70% higher specific capacitance (177 F g−1) than the pure porous carbon (106 F g−1) in 6 M KOH. Among these electrolytes, the composite exhibited an enhanced electrochemical performance in KOH electrolyte due to its smaller hydrated ion radius, high ionic mobility and lower equivalent series resistance than Na2SO4.